Adhesion, proliferation and osteogenic differentiation of human MSCs cultured under perfusion with a marine oxygen carrier on an allogenic bone substitute. (2nd January 2018) - Le Pape, Fiona; Richard, Gaëlle; Porchet, Emmanuelle; Sourice, Sophie; Dubrana, Frédéric; Férec, Claude; Polard, Valérie; Pace, Richard; Weiss, Pierre; Zal, Franck; Delépine, Pascal; Leize, Elisabeth
Abstract: Tissue engineering strategies have been developed to optimize osseointegration in dental implant surgery. One of the major problems is the non-homogeneous spatial cell distribution in the scaffold, as well as subsequent matrix production. Insufficient nutrient and oxygen supplies inside the scaffold are factors in this phenomenon. To mediate this gradient formation, we have implemented a perfusion culture method to seed human bone marrow mesenchymal stem cells (MSCs) into three-dimensional (3-D)-allogenic bone scaffolds in combination with a marine haemoglobin, HEMOXCell ®, for oxygen delivery. Cell culture was performed under static and perfusion conditions, with standard and osteogenic media, with and without HEMOXCell ® . The cell seeding efficiency, as well as MSC/scaffold cytocompatibly were assessed using viability and proliferation assays. Scaffolds' cellularization and extracellular matrix (ECM) formation were analyzed using scanning electron microscopy and histological staining. Cell differentiation was investigated with osteogenic biomarkers gene expression analysis. The perfusion culture was observed to significantly promote MSC proliferation and differentiation throughout the scaffolds, especially when using the induction medium w/HEMOXCell ® . Our data suggest that perfusion culture of MSC into allogenic bone substitute with HEMOXCell ® as a natural oxygen carrier is promising for tissue engineering applications to oxygenate hypoxic areas and to promote cellular proliferation.